Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Find $$\Pi^{7}_{k=1}(z-e^{-k\pi i})$$

Calculating by hands seems possible but it requires a lot of work. Is there any tricks? Periodicity helps?

share|cite|improve this question
up vote 4 down vote accepted

As you noted, periodicity is very helpful. $e^{-k\pi i} = e^{\pi i} = -1$ for odd $k$ and $e^{-k\pi i} = e^{2\pi i} = 1$ for even $k$. Your expression then simplifies to $$(z+1)^4(z-1)^3 = (z^2 - 1)^3(z+1)$$

share|cite|improve this answer
Thanks! It should be the fastest and most beautiful solution. – John Hass Oct 28 '12 at 15:45

Using Euler's formula, $e^{i\pi}=\cos(\pi)+i\sin(\pi)=-1,$ so $(e^{i\pi})^{2r+1}=-1$ and $(e^{i\pi})^{2r}=1$

$1\le k\le 2n+1 $ contains $n+1$ odd ,$n$ even values of $k$.

So, $$\Pi^{2n+1}_{k=1}(z-e^{-k\pi i})=\{z-(-1)\}^{n+1}(z-1)^n=(z+1)(z^2-1)^n$$

Here $n=3$.

$1\le k\le 2n $ contains $n$ odd ,$n$ even values of $k$.

So, $$\Pi^{2n}_{k=1}(z-e^{-k\pi i})=\{z-(-1)\}^n(z-1)^n=(z^2-1)^n$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.